2015
DOI: 10.1097/iop.0000000000000363
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-Related Ophthalmic Disease. Part I

Abstract: Patients presenting with orbital inflammatory lesions should have biopsies obtained whenever possible. The examining pathologist should routinely look for features of IgG4-ROD, and if found, the patient should be investigated for other organ involvement. Early treatment may prevent destructive changes in affected tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 60 publications
0
47
0
2
Order By: Relevance
“…With the increasing understanding of the pathology, clinical-radiological features and clinical implications of IgG4 disease over the recent years, 16,17 we believe that this specific group of disease may represent a considerable proportion of the biopsied cases in the future. A recent Japanese report described, as many as, 21.4% of their presumed 'lymphoproliferative disease' cases were of IgG4-ROD.…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing understanding of the pathology, clinical-radiological features and clinical implications of IgG4 disease over the recent years, 16,17 we believe that this specific group of disease may represent a considerable proportion of the biopsied cases in the future. A recent Japanese report described, as many as, 21.4% of their presumed 'lymphoproliferative disease' cases were of IgG4-ROD.…”
Section: Discussionmentioning
confidence: 99%
“…1d). Sicca symptoms are often less severe in IgG4-RD than in Sj€ ogren's syndrome and, when present, typically respond well to immunosuppressive therapy [31][32][33][34][35]. Orbital pseudotumours affect the lacrymal gland most often but can also occur in other orbital regions.…”
Section: Overview Of Clinical Manifestationsmentioning
confidence: 99%
“…Orbital pseudotumours affect the lacrymal gland most often but can also occur in other orbital regions. Extra-ocular muscle involvement (frequently termed 'orbital myositis' in the days before the recognition of IgG4-RD) can present with exophthalmos and the restriction of ocular movements [32,33] (Fig. 1e,f).…”
Section: Overview Of Clinical Manifestationsmentioning
confidence: 99%
“…The orbital tissue is also often involved, with a prevalence of 3.6-12.5% [1,[7][8][9][10]. The current diagnostic criteria of IgG4-RD include [11]: single or multiple organ swelling, either symmetrically or locally, with the formation of a mass; serum IgG4>1.35 g/L; and [12], so IgG4-RD cannot be completely excluded using this parameter [13]. Recent studies have shown that the serum IgG4 + /IgG + ratio may be more sensitive and specific in the diagnosis of early and single organ-limited development of IgG4-RD [14][15][16].…”
Section: Discussionmentioning
confidence: 99%